2008
DOI: 10.1089/jmf.2007.574
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Evaluation of the Safety and Tolerance of Medicinally Ingested Vinegar in Individuals with Type 2 Diabetes

Abstract: Vinegar (VIN) ingestion at mealtime reduces postprandial glycemia and may benefit individuals with diabetes; hence, the medicinal use of VIN has increased in recent years. This study examined the safety and tolerance of medicinally ingested VIN in type 2 diabetics. Participants (n = 27) were stratified by gender, age, and body mass and randomized into three groups: commercial VIN pills (the reference treatment [REF] (30 mg of acetic acid daily), pickles (PCK) (approximately 1,400 mg of acetic acid daily), or V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…80 Most side effects from vinegar are gastrointestinal in nature. 81 However, hypoglycemia has been reported in type 1 diabetes patients with gastroparesis. 82 Oropharyngeal inflammation and caustic esophageal injury have also been reported.…”
Section: Vinegarmentioning
confidence: 99%
“…80 Most side effects from vinegar are gastrointestinal in nature. 81 However, hypoglycemia has been reported in type 1 diabetes patients with gastroparesis. 82 Oropharyngeal inflammation and caustic esophageal injury have also been reported.…”
Section: Vinegarmentioning
confidence: 99%
“…The only 2 non-English articles were in Persian. 14 , 22 Five were parallel group randomized controlled trials, 14 , 17 , 18 , 21 , 24 5 were crossover randomized controlled trials, 12 , 16 , 22 , 23 , 25 1 was a nonrandomized controlled trial, 20 and 1 was a single-arm before-and-after study. 19 The subjects were treated with diet, oral hypoglycemic agents, or insulin.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported PPG levels at 30 minutes, 16 , 17 , 19 , 21 , 25 4 studies at 60 minutes, 16 , 17 , 19 , 25 and 3 studies at 90 and 120 minutes. 17 , 19 , 25 Pooled mean difference of PPG levels between control and vinegar groups were 0.88 mmol/L (95% confidence interval [CI] = 0.51, 1.25) at 30 minutes (n = 102), 0.45 mmol/L (95% CI = −0.31, 1.21) at 60 minutes (n = 92), 0.10 mmol/L (95% CI = −0.52, 0.73) at 90 minutes (n = 74), and 0.05 mmol/L (95% CI = −1.11, 1.20) at 120 minutes (n = 74). Three studies reported FPI at 30 and 60 minutes 17 , 19 , 25 and 2 studies at 90 and 120 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this raises concerns about the appropriateness and safety of this advice, as ingestion of vinegar products have been reported to be linked with oesophageal injury, 7,8 biochemical disturbances, 9 dental erosion 10 and acute pancreatitis 11 and symptoms such as acid reflux, burping/ flatulence and changes in bowel habit. 12 It could further be argued that the scientific evidence currently available is not sufficient to warrant such health claims.…”
Section: Introductionmentioning
confidence: 99%